Recursive Inverse Adaptive Filtering for Fading Communication Channels - Jaar, Faris Yousef Shokri (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Adaptive filtering is an important and rapidly developing discipline in the signal processing and communications field. Many different algorithms were developed throughout the years. LMS and RLS being the most well-known and studied of the algorithms. Like in many disciplines in engineering there exists many disadvantages in these algorithms and so variations were proposed. The main parameters sought after in a new algorithm were convergence speed, stability, and computational complexity. LMS suffers in the former as it has generally low convergence speed. Meanwhile, RLS main disadvantage is the computational complexity it introduces, in addition to being unstable in varying channel settings. RI adaptive filtering algorithm proposed in 2009 provides some solutions to the aforementioned issues. In this thesis, the use of the RI algorithm in common communication channel setting is simulated. The performance of the algorithm is studied and compared to some other adaptive filtering algorithms in terms of BER. Both channel estimation and channel equalization performances are investigated and commented upon. The conclusions reached will be that RI outperforms RLS in terms of convergence speed and computational complexity in all cases studied while giving similar results to NLMS in frequency selective channels but outperforming it in flat fading channels. Keywords: Adaptive filter, recursive inverse, RLS, communication channel

ÖZ: Uyumlu filtreleme sinyal işleme ve iletişim alanının önemli ve gelişmekte olan bir disiplinidir. Alanın gelişme sürecinde farklı uyumlu filtre algoritmaları geliştirilmiştir. Least Mean Squares (LMS) ve Recursive Least Squares (RLS) algoritmaları en fazla bilinen ve başarımı araştırılan algoritmaların başında gelmektedir. Geliştirilen algoritmaların olumlu ve olumsuz yönleri bulunmakta ve araştırmacılar uygulamaya özge farklı geliştirmeler önermektedirler. Bu kapsamda en önemli başarım parametreleri yakınsama hızı, kararlılık ve hesaplama karmaşıklığıdır. LMS genel olarak düşük yakınsama hızına sahiptir. RLS ise, yüksek hesap karmaşıklığına ve kararlılık sorunlarına sahip olmakla birlikte, hızlı ve ilintili gürültü ortamlarında bile çalışabilen bir algoritmadır. 2009 yılında önerilen Recursive Inverse (RI) uyarlanır algoritması, yukarıda bahsedilen olumsuz yanların gelişmesine katkı koymaktadır. Tezde, RI algoritmasının iletişim kanallarında başarımı benzetimler yoluyla incelenmiştir ve farklı güncel algoritmalarla Bit Hata Oranı (BER) açısından karşılaştırılmıştır. Kanal kestirimi ve kanal dengeleme başarımları incelenerek ulaşılan BER değişimleri gözlemlenmiştir. RI algoritmasının, RLS, LMS ve Normalized Least Mean Squares (NLMS) algoritmalarından yakınsama hızı ve hesaplama karmaşıklığı açısından avantajları farklı ortamlarda belirlenmiş ve sunulmuştur. Anahtar Kelimeler: Uyumlu filtre, sönümlemeli haberleşme kanalı, kanal dengeleme
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2019. Supervisor: Prof. Dr. Aykut Hocanın.
Keywords: Electrical and Electronic Engineering; Adaptive signal processing; Signal processing--Statistical methods; Adaptive filters; Adaptive filter; recursive inverse; RLS; communication channel